The effectiveness and safety of cariprazine in schizophrenia patients with negative symptoms and insufficient effectiveness of previous antipsychotic therapy: an observational study. (May 2021) - Rancans, Elmars; Dombi, Zsófia Borbála; Mátrai, Péter; Barabássy, Ágota; Sebe, Barbara; Skrivele, Iveta; Németh, György
Abstract : The aim of the study was to examine the effectiveness and safety of cariprazine in routine psychiatric settings on schizophrenia patients with negative symptoms who have been treated with antipsychotics previously but without sufficient success. This was an open-label, flexible-dose, 16-week, observational study in Latvia. The primary outcome measure was an array of anamnesis-based clinical questions on schizophrenia symptoms rated on a seven-point scale. Other outcome measurements were the clinical global impression improvement (CGI-I) and severity (CGI-S) scales. Safety parameters included spontaneous reports of adverse events and specific assessments of extrapyramidal side-effects. A mixed model for repeated measures was fit to the data to evaluate the mean change from baseline for all visits. A total of 116 patients enrolled in the study (completion: 83%). Change from baseline to termination in symptom control was statistically significant (−7.3; P < 0.001), with the most improvement in negative symptoms (−6.3; P < 0.001). Over 70% of patients improved minimally or much based on the CGI-I scores at the final visit, and the CGI-S scores indicated an overall improvement in severity from moderately to mildly ill. 40% of patients experienced treatment-emergent adverse events. Over 70% of doctors were satisfied with the effectiveness and tolerability of cariprazine. Cariprazine significantly improved negative symptoms in schizophrenia patients. Abstract : Supplemental Digital Content is available in the text.